A new series of azobenzene-bridged metal-free organic dyes and application on DSSC. (November 2017) - Chiu, Kuo Yuan; Ha Tran, Thai Thi; Chang, Sheng Hsiung; Yang, Te-Fang; Su, Yuhlong Oliver
Abstract: A series of novel azobenzene-based dyes were designed and synthesized using azobenzene as the π -spacer unit to connect diarylamino and cyanoacetic acids for construction of the D–π–A conformation. The introduction of a thienyl into the anchor group (A) could lead to a red-shift in the absorption spectra and λonset of the dyes. When the diaryamino substituent was changed from methyl to methoxyl, a slight negative shift in the first oxidation peak could be observed. The spin density distribution of the cation radicals of the four dyes was also investigated. The qualitative order of the stability of these four cation radicals was found to beTA4 > TA3 > TA2 > TA1 in air. They were then employed as the sensitizer in organic dye-sensitized solar cells to achieve the highest power conversion efficiency (PCE) of 4.78% under AM 1.5 conditions. By systematically changing the donor and acceptor unit of these dyes, the new record on PCE with using azobenzene as the π -spacer unit was achieved. Graphical abstract: Highlights: A series of novel azobenzene-based dyes were synthesized. The stability order of these four dyes cation radicals was found to beTA4 > TA3 > TA2 > TA1 in air. The new record on PCE with using azobenzene as the π -spacer unit was achieved.